2020
DOI: 10.3389/feart.2020.536332
|View full text |Cite
|
Sign up to set email alerts
|

Electric and Magnetic Recordings by Chieti CIEN Station During the Intense 2016–2017 Seismic Swarms in Central Italy

Abstract: We monitored electric and magnetic fields synchronously and continuously in an Italian area prone to moderate-to-high magnitude seismic activity. Identifying and monitoring of potential precursors may contribute to risk mitigation. A decade after the Central Italy Electromagnetic Network started, nine strong shakes with magnitudes between 5.0 and 6.6 occurred in Central Italy between August 2016 and January 2017. The events produced a fault offset of up to 2.8 m along a NNW-SSE normal fault system, 75 km long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Furthermore, Schekotov et al ( 2017) [93] found the same ULF/ELF emissions before the recent Kumamoto EQs as well, and it seems that these ULF/ELF emissions are likely generated for any EQs, either inland-fault-type or oceanic-sea-type EQ. Recently, Fidani et al (2020) [81] presented further evidence of these ULF/ELF emissions in the same frequency for the EQs in Europe with the use of their Italian network. Their characteristics, such as impulsive nature, frequency range, and lead time, are very consistent with our statistical summary by Schekotov and Hayakawa (2017) [82] and Hayakawa et al (2019) [83], but unfortunately, they did not provide any statistical study as ours.…”
Section: Atmospheric Effectsmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, Schekotov et al ( 2017) [93] found the same ULF/ELF emissions before the recent Kumamoto EQs as well, and it seems that these ULF/ELF emissions are likely generated for any EQs, either inland-fault-type or oceanic-sea-type EQ. Recently, Fidani et al (2020) [81] presented further evidence of these ULF/ELF emissions in the same frequency for the EQs in Europe with the use of their Italian network. Their characteristics, such as impulsive nature, frequency range, and lead time, are very consistent with our statistical summary by Schekotov and Hayakawa (2017) [82] and Hayakawa et al (2019) [83], but unfortunately, they did not provide any statistical study as ours.…”
Section: Atmospheric Effectsmentioning
confidence: 90%
“…Even though a statistical study on this phenomenon was first published by Schekotov et al (2007) [78], this effect is not so popular either in the academic society. However, recently, Fidani et al (2020) [81] confirmed the presence of this ULF/ELF impulsive radiation with their Italian network and suggested it as a short-term EQ predictor, but unfortunately, they have not yet provided any statistical study as in [78,80,82,83].…”
Section: Analysis Methods Of Ulf/elf Electromagnetic Radiationmentioning
confidence: 97%
“…After having stressed that a statistical correlation between two time series does not generally mean that they are physically related (Aldrich, 1995), the hypothesis concerning a physical link between EBs and EQs was studied. A recent observation of magnetic pulses recorded before strong EQs in Central Italy provided recorded magnetic intensities with a diffuse current model (Fidani et al, 2020). This model can push back to the hypocenter region the causal connection of physical events, even if the deduced magnetic inductions in the ionosphere must be demonstrated to be able to modify the electron pitch angles.…”
Section: Discussionmentioning
confidence: 99%
“…Even if other processes have been proposed more recently, such as the injection of radioactive substances and charged aerosols into the atmosphere, leading to a change in the vertical electric current in the atmosphere and to a modification of the electrical field in the ionosphere (Sorokin et al, 2001), from a solidstate physics perspective (Freund, 2011), and radioactive ionization to model the lithosphere-atmosphere-ionosphere-magnetosphere coupling by the latent heat flux (Pulinets et al, 2015), by AGW (Yang et al, 2019;Piersanti et al, 2020). Recent measurements of magnetic pulses on the occasions of strong EQs (Bleier et al, 2009;Orsini, 2011;Nenovski, 2015) have suggested an efficient process which may influence the ionosphere (Fidani et al, 2020). In this latter work, the magnetic data analysis at the Chieti Station of the Central Italy Electromagnetic Network, performed using two independent sample systems of the same signal, showed that a large number of pulses were recorded in the ELF band below 10 Hz with amplitudes mostly in the range of 2.5-80 nT.…”
Section: Different Precursors Combinedmentioning
confidence: 99%
See 1 more Smart Citation